HUBUNGAN ANTARA KONTRIBUSI EDUCATOR OLEH PERAWAT DALAM DISCARE PLANNING DENGAN TINGKAT KEDISIPLINAN PASIEN GAGAL GINJAL KRONIK YANG MELAKUKAN HEMODIALISA SECARA RUTIN - Rina Situmorang, Paskah; Lingga, Rugun Togianur; Berutu, Heriaty; Herlina, Meriani; Noradina, Noradina; Silalahi, Bernita; Ritonga, Yuni Shanti; Harefa, Sehardi Natal; Manurung, Sarida Surya (Jurnal Ilmiah Keperawatan IMELDA, 2024)
ABSTRACT Hemodialysis is dialysis therapy as a kidney replacement in patients with CKD. One of the problems that cause hemodialysis failure is the problem of compliance in patients with chronic kidney failure who undergo hemodialysis therapy. Therefore, the role of health workers is very much needed in providing understanding to patients regarding discharge planning in order to get better care to achieve the patient's quality of life. If the patient is not disciplined in maintaining his life by obediently carrying out hemodialysis therapy according to the doctor's recommendations, shortness of breath, edema, ascites will occur and will cause many long-term complications which will ultimately increase mortality. With quality instructions from nurses or a good understanding of discharge planning, it is hoped that it can improve the discipline of CKD patients in carrying out hemodialysis therapy. This study aims to determine whether there is a relationship between the contribution of educators by nurses in discharge planning and the level of discipline of chronic kidney failure patients who undergo regular hemodialysis at RSU IPI Medan. This type of quantitative research with a correlation research design. Data collection used was an educator contribution questionnaire by nurses in discharge planning which consisted of 21 questions. The population in this study was all CKD patients undergoing hemodialysis therapy, totaling 52 people. With an accidental sampling technique. The research results were tested using the Chi-Square test with a (p) value of <0.001 <0.05, meaning that there is a relationship between the provision of discharge planning and the level of discipline of CKD patients undergoing hemodialysis therapy, so it is hoped that all health workers will provide clear information to patients regarding the importance of carrying out hemodialysis therapy so that the patient's quality of life is more optimal.